Local Organic Certification in Northern Thailand: The Role of Discourse Coalitions in Actor-Networks - Wyatt, Brett (The International Journal of Sociology of Agriculture and Food, 2010)
An actor-network approach is used to analyse a local organic agriculture network in Northern Thailand. This network is centred around local organic standards developed by discourse coalitions with similar social concerns about organic agriculture. Local standards were developed through the translation of existing, international standards into production processes directly addressing the social concerns by discourse coalitions of farmers, retailers, and consumers, leading to the establishment of the Northern Organic Standards Organization (NOSO). The standards are communicated symbolically to consumers through labels and logos. When applying for national recognition as an organic certifying body through the National Bureau of Agricultural Commodity and Food Standards (ACFS) of Thailand, NOSO found that local standards must comply in total to all International Federation of Organic Agriculture Movements (IFOAM) standards for accreditation. The impasses between local concerns and international policies led to what I call a reflexive translation of the appropriateness of international accreditation for the local organic certifying body, resulting in new policies supporting local concerns addressed by the existing body of local organic standards.